QRIS Technology Adoption in Traditional Markets:A Community-Based Educational Initiative in Mataram City - Yunia Ulfa Variana; Rahmat Akbar Kurniawan (Pendidikan Al-Gafari, 2026)
The rapid expansion of digital financial infrastructure throughout Indonesia creates both significant opportunities and persistent structural barriers for traditional marketplace vendors a socioeconomic cohort that remains underrepresented in the formal digital economy. This community engagement initiative documents and evaluates a comprehensive seven month QRIS (Quick Response Code Indonesian Standard) awareness and capacity building effort conducted across two major traditional markets in Mataram City, West Nusa Tenggara: Pasar Mandalika (Sandubaya) with 65 traders and Pasar Kebon Roek (Ampenan) with 41 traders. The intervention employed a five-component model encompassing baseline assessments, group awareness sessions, practical skills workshops, personalized technical assistance, and comprehensive outcome evaluation. This structured approach engaged 106 traders over an eight-month implementation period from August 2025 through February 2026. Using a quasi experimental framework with pre intervention and post intervention measurements, the research tracked improvements in QRIS literacy, operational competency, and documented merchant account registrations. Results demonstrated substantial and statistically significant improvements across all dimensions: QRIS awareness increased from 35.9% to 89.4%, hands on scanning proficiency rose from 12.4% to 78.6%, and verified merchant account activation climbed from 8.9% to 61.3%. The study integrates established frameworks including Davis’s Technology Acceptance Model, Rogers’ Diffusion of Innovations Theory, and Indonesia’s National Financial Inclusion Strategy (2021 - 2025). Qualitative investigation identified four primary adoption barriers: gaps in functional digital literacy, insufficient confidence in settlement mechanisms, limited regional language support, and apprehension regarding tax registration consequences of QRIS participation. The research concludes with evidence based recommendations for designing scalable, contextually appropriate digital payment adoption initiatives targeting informal sector participants in Indonesia’s secondary urban regions